ONA TILI SINTAKSISI FANINI O‘QITISHDA MODELLASHTIRISH METODI ZAMONAVIY PEDAGOGIK TEXNOLOGIYA SIFATIDA - Roʻziyeva, S.H. (SCIENCE and SOCIETY, 2022)
The article discusses the use of modeling technology as a modern approach in the course of higher education native language syntax classes. The article also provides information about the necessity and benefits of modeling in education. Mathematical and natural methods of modeling technology are compared.